Peranan LMS Terhadap Evektivitas Belajar Mahasiswa Universitas XYZ Dengan Metode Pembelajaran Multi Channel Learning - Yoan Infaqiatullah Zahra; Asrul Sani (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
In the current era of globalization, various things can be associated with information technology. This is because information technology can support daily human activities in various fields, especially education. In this study, the authors wanted to know the role of LMS on the effectiveness of student learning at XYZ University using the Multi Channel Learning method. The research methodology used by the author uses the method of observation and literature study. By conducting this research, the authors hope to provide many benefits to the world of education, especially XYZ University, so that readers can see how LMS plays a role in the effectiveness of learning for students. The results of the study prove that the teaching and learning process using LMS can make it easier for students and lecturers to interact anywhere. In addition, the teaching and learning process is well documented so that it can be accessed at any time by students and lecturers.